EXAMINING THE IMPACT OF INFORMATION TRANSPARENCY VIA @GANJAR_PRANOWO'S INSTAGRAM CONTENT ON PUBLIC TRUST IN PANDEMIC SITUATION - Ayu Rachmahwati; Hasanah, Khuswatun (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2023)
In 2020, Central Java Province, led by Governor Ganjar Pranowo, stood out in the Saiful Mujani Research Center (SMRC) survey, ranking first among regional governments with a 73% approval rate for its swift and responsive pandemic policies, surpassing the national standard of 59%. This success prompted an investigation, particularly as Instagram emerged as Ganjar Pranowo's primary tool for communicating his governance efforts during the pandemic. Instagram, as a platform, demonstrated greater responsiveness than other social media platforms. Observations revealed heightened interaction levels on Instagram compared to Twitter, evident in increased comments and likes. Ganjar Pranowo strategically utilized Instagram for public interaction, disseminating information, fostering community support, and educating the public about COVID-19. This study explores the realm of Political Communication through online mass media, emphasizing the evolving role of mass media and Ganjar Pranowo's adept use of it for open communication during the pandemic. Employing a quantitative approach, the research utilized questionnaires distributed to @ganjar_pranowo Instagram followers in Central Java, complemented by interviews with selected informants. Simple linear regression analysis, grounded in the principles of Good Governance, served as the theoretical framework. Findings analyzed using SPSS 25.0, revealed a significant impact of information transparency on public trust. With a calculated F-value of 146.267 and a significance level of 0.000 (< 0.05), the study suggests that information transparency through Instagram content influences public trust in pandemic management by approximately 59.9%, with 40.9% influenced by unexplored variables.